The financial crisis of 2008 and the developing countries - Wim Naudé (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2009)
Following the financial crisis that broke in the US and other Western economies in late 2008, there is now serious concern about its impact on the developing countries. The world media almost daily reports scenarios of gloom and doom, with many predicting a deep global recession. This paper critically discusses this and concludes that as far as the developing countries are concerned, a bit more optimism may be warranted. Although without doubt there are particular countries that will be adversely affected, there will also be countries that may be less affected, may avoid recession, and may recover sooner than expected. Six major reasons for this conclusion are discussed. Without this resilience in the developing world, prospects for the world's richer countries would be much bleaker. Finally, some options available to the developing countries for minimizing the impact of the crisis are discussed. The crisis accentuates the urgent need for accelerating financial development in developing countries, both through domestic financial deepening, domestic resource mobilization, and reform of the international financial system.
Keywords: F34; F35; G14; O16; 330; financial crisis; developing countries; development finance; financial development